Cloud computing adoption in organisations: review of empirical literature - Hassan, Haslinda; Mohd Nasir, Mohd Herry; Khairudin, Norhaiza (EDP Sciences., 2017)
This study reviews literature on cloud computing adoption in organisations to identify its influential factors and its operationalisation in prior literature.We classify the factors that influence the cloud computing adoption using the three contexts suggested by the Technology Organisation-Environment(TOE) framework, namely, technology, organisation, and environment. The finding suggests that the influences of these factors vary across studies and most of the studies have operationalised cloud computing adoption using intention to adopt cloud computing or binary variable, rather than the actual use of the technology.